2011
DOI: 10.1016/j.ultsonch.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced creaming of milk fat globules in milk emulsions by the application of ultrasound and detection by means of optical methods

Abstract: The effects of application of ultrasonic waves to recombined milk emulsions (3.5% fat, 7% total solids) and raw milk on fat destabilization and creaming were examined. Coarse and fine recombined emulsions (D[4,3]=9.3 μm and 2.7 μm, respectively) and raw milk (D[4,3]=4.9 μm) were subjected to ultrasound for 5 min at 35°C and 400 kHz or 1.6 MHz (using a single transducer) or 400 kHz (where the emulsion was sandwiched between two transducers). Creaming, as calculated from Turbiscan measurements, was more evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…Recent work has shown the ability of ultrasound in standing wave fields to initiate rapid separation of fat globules in recombined milk fat emulsions [6,18] and natural whole milk [7,19]. These studies have shown that ultrasound at frequencies greater than 600 kHz and energy levels up to 583 W/L do not disrupt the physical integrity of the milk fat globules [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown the ability of ultrasound in standing wave fields to initiate rapid separation of fat globules in recombined milk fat emulsions [6,18] and natural whole milk [7,19]. These studies have shown that ultrasound at frequencies greater than 600 kHz and energy levels up to 583 W/L do not disrupt the physical integrity of the milk fat globules [19].…”
Section: Introductionmentioning
confidence: 99%
“…The technique using ultrasound waves to initiate separation of fat globules from milk has been recently reported by Juliano et al [2,3] using a recombined emulsion and Leong et al [4] using natural milk. Milk fat separation rates many times faster than natural creaming have been reported using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the input of ultrasound to the milk system resulted in heat generation over time, causing the overall system to increase in temperature. Studies by Juliano et al [2,3] demonstrated the enhanced ultrasonic-assisted fat separation using reconstituted milk fat emulsions at 400 kHz, 1 and 2 MHz ($35 W/L per transducer used). These studies were performed with an initial temperature of 35°C, on the supposition that the higher proportion of liquid milk fat at these temperatures would be more readily separable by ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Juliano et al [56] demonstrated the concept of ultrasonic separation for natural whole milk in small test tubes of 7-mL volume and was later successful in scaling this process up to 6 L using a recombined milk emulsion [57]. Leong et al [69] established suitable ultrasonic parameters that enable successful separation of natural whole milk in large scale, demonstrating the importance of energy density and effectiveness of high-frequency ultrasound (1 and 2 MHz) to separate the small fat globules distributed in milk (*4 lm diameter).…”
Section: Ultrasonic Separation Of Fatmentioning
confidence: 99%